The awareness of first aid management on construction site in Malaysia / Khairul Anwar Azman - Azman, Khairul Anwar (Faculty of Architecture, Planning and Surveying, 2015)
This research paper is about the safety awareness on construction in Malaysia. There are many management about safety inside the construction Malaysia. One of the management that the researcher is research about is First Aid Management. This research paper consist of study the construction personnel awareness on the safety and first aid management on construction site. It also to find the action of the respondent and their employer about the safety management on the site. The result from this research will define the level of awareness of construction personnel on the First Aid Management and safety awareness on the construction site. It also want study the what action taken by the construction personnel when there are accidents or incidents happen on the construction site.